2010
DOI: 10.1086/657397
|View full text |Cite
|
Sign up to set email alerts
|

New Light on Human Prehistory in the Arabo-Persian Gulf Oasis

Abstract: The emerging picture of prehistoric Arabia suggests that early modern humans were able to survive periodic hyperarid oscillations by contracting into environmental refugia around the coastal margins of the peninsula. This paper reviews new paleoenvironmental, archaeological, and genetic evidence from the Arabian Peninsula and southern Iran to explore the possibility of a demographic refugium dubbed the "Gulf Oasis," which is posited to have been a vitally significant zone for populations residing in southwest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 164 publications
(188 reference statements)
0
90
0
Order By: Relevance
“…The paucity of archaeological material means opinions are currently divided regarding the subsistence base of these early populations. Whilst some authors link the archaeological finds from this period to mobile herder-gatherers (Drechsler, 2009), others suggest they were left by huntergatherer populations (Charpentier, 2008;Rose, 2010) whose footprint on the landscape is likely to be less visible today. Furthermore, it is suggested that huntergather groups are more likely to have concentrated in areas of the landscape with greater ecological diversity and resource availability, which during the earliest Holocene is more likely to have been within the now submerged Arabian Gulf basin or within the al-Hajar Mountains and the alluvial piedmont bahadas.…”
Section: Climate -Human Implications During the Neolithicmentioning
confidence: 99%
“…The paucity of archaeological material means opinions are currently divided regarding the subsistence base of these early populations. Whilst some authors link the archaeological finds from this period to mobile herder-gatherers (Drechsler, 2009), others suggest they were left by huntergatherer populations (Charpentier, 2008;Rose, 2010) whose footprint on the landscape is likely to be less visible today. Furthermore, it is suggested that huntergather groups are more likely to have concentrated in areas of the landscape with greater ecological diversity and resource availability, which during the earliest Holocene is more likely to have been within the now submerged Arabian Gulf basin or within the al-Hajar Mountains and the alluvial piedmont bahadas.…”
Section: Climate -Human Implications During the Neolithicmentioning
confidence: 99%
“…Five such claims currently vie for attention, all with date brackets similar to those of the Levant exit, four with fossils and one with cultural evidence. The latter is at Jebel Faya on the Arabian Peninsula, where lithics with affinities to the Late Middle Stone Age in northeast Africa date between 127 ka and 95 ka [18] (reviewed by Petraglia et al [16]; Rose [72]). …”
Section: Review Of Out-of-africa Modelsmentioning
confidence: 99%
“…A discontinuous occupation of the Arabian Peninsula during the Middle Paleolithic is also suggested by a high technological diversity (Petraglia and Alsharekh, 2003;Rose, 2007a;Crassard, 2008;Petraglia and Rose, 2009;Delagnes et al, 2012) whose significance (diachronic changes vs. regional synchronic diversity) remains however questionable since it relies on few dated and stratified records. In between periods of moisture and hyper-aridity peaks, the Arabian populations endured a series of climate and environmental degradations which may have resulted in contractions of settlements into environmental refugia (Bailey, 2009;Rose and Petraglia, 2009;Rose, 2010). This environmental refugia model is prominent in the literature relating to the East African Middle Stone Age (Clark, 1989;Lahr and Foley, 1994;Ambrose, 1998;Basell, 2008), and is discussed in the context of the Azraq Basin in Jordan by Cordova et al (2013), but remains largely theoretical in the Arabian Peninsula during MIS 5, due the lack of chronological and environmental data from stratified archaeological contexts.…”
Section: Mis 5 Inter-regional Expansionsmentioning
confidence: 99%